(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Anxiety disorders are reported in the different age group of people in the urban area. Objective: The purpose of the present study was to determine the level of anxiety disorder among urban elderly people. Methodology: This cross-sectional community based study was carried out from January to December 2016 at Bakolia, Chawkbazar urban area of Chittagong, Bangladesh.The individuals who were aged 60 years and above were interviewed by using convenient sampling. Face to face interview was done with semi structural questionnaire. Results: Out of 300 respondents female respondents were higher in number which was 168(56%) respondents; however, 71.7%, respondents were in 60 to 69 age groups. Majority of respondents did not have any income which was 72(60.0%) subjects. Most of the respondents were suffering from hypertension which was 198(66.0%) respondents. In urban areas 82(27.3%) subjects did not have anxiety disorder, while 133(44.3%) respondents had mild anxiety disorder, 63 (21.0%) respondents had moderate and 22 (7.3%) respondents had severe anxiety disorder. Furthermore, 192 (64.0%) respondents who were concerned about their finance had anxiety disorder. 160 (53.3%) were concerned about their health had anxiety disorder. Conclusion: In conclusion majority urban dwelling elderly people are suffering from anxiety disorders. Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 137-141